KETERKAITAN ANTAR SEKTOR DALAM PEREKONOMIAN DAERAH ISTIMEWA ACEH MELALUI ANALISIS TABEL I – O - Zuliani - (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2011)
Lingkage of economy between sectors in economic either economy of a country or a distric is very important to be analized. To know the economics interlated in Aceh special province, this research will observe about linkages between sectors through input â€“ output table analizing. Data that used in this research was secondary data that taken from statistic center. The date were Table I-O 1988 and I-O 1997. Eight relative dominant sectors chosen, namely rice/padi, plantation, animal husbandry, food industry, drink, tobacco and oil and natural gas sectors. Model that used was input-output model. Variabel that used: matrix output domestic product (P), matrix identity (I), input matrix coeficient from domestic input (Ad) and final request matrix sector toward product (Fd). Based on the result explained that lingkages between sectors in special Aceh province economy having change for several years. Every sector had different lingkages stage with others sector that shown through the number of the input and output sector and the sum of input coeficient that required by that sector. Inplication of result mentioned that economic sectors will have changing and increasing if technology factor and coeficient stage of every economy sector predicted in every bussiness.Â